Syndesmotic Overload in 3-Component Total Ankle Replacement. (March 2020) - Ruiz, Roxa; Susdorf, Roman; Krähenbühl, Nicola; Barg, Alexej; Hintermann, Beat
Background: Mobile-bearing total ankle replacement (TAR) potentially enables motion at the tibial implant–polyethylene insert (PI) interface. Such additional freedom of movement may overload periarticular ligaments and subsequently result in coronal translation of the talus. The aim of this study was to assess whether syndesmotic overload affects clinical and radiographic outcomes following mobile-bearing TAR and whether tibiofibular fusion is an effective treatment option. Methods: Thirty-one patients who underwent revision surgery for syndesmotic overload after mobile-bearing TAR were retrospectively analyzed. Clinical and radiographic outcomes were assessed before and after index TAR, preoperatively to revision surgery, and at the last follow-up after revision surgery. Computed tomography scans were also analyzed. Results: Ankles with lateral talar translation prior to revision surgery were about 10 times more likely to have valgus tibial implant position ( P = .003). A wide tibiofibular distance at the level of the syndesmosis after index TAR was associated with an increased hindfoot moment arm at revision surgery ( P = .025). Decrease of PI height at revision surgery and a PI fracture were evident in 10 (32%) and 4 (13%) cases, respectively. Talar cyst formation at revision surgery was evident in 12 (39%) cases. Tibiofibular fusion was effective in restoring function of the replaced ankle and providing pain relief. Conclusion: Syndesmotic overload impaired clinical and radiographic outcomes after mobile-bearing TAR. Proper implant positioning and additional realignment procedures may prevent overload of periarticular soft tissue structures after mobile-bearing TAR. Level of Evidence: Level IV, retrospective case series.